Branchial cleft cyst - Valentino, M. (Springer International Publishing AG, 2013)
Branchial cleft cysts are benign lesions caused by anomalous development of the brachial cleft. This report describes a 20-year-old girl with swelling on the right lateral aspect of the neck, which expanded slowly but progressively. The clinical suspicion was that of a branchial cleft cyst. Sonography revealed a homogeneously hypo- to anechoic mass with well-defined margins and no intralesional septa. Color Doppler reviewed no internal vascularization. The ultrasound examination confirmed the clinical diagnosis of a second branchial cleft cyst, demonstrating the cystic nature of the mass and excluding the presence of complications. For superficial lesions like these, ultrasound is the first-level imaging study of choice because it is non-invasive, rapid, low-cost, and does not involve exposure to ionizing radiation.